Personality traits and alcohol consumption: Secondary analysis of the Self‐Match Study. (2nd May 2022) - Hell, Morten Ellegaard; Müller, Anders; Horn, Christina Gehling; Søgaard Nielsen, Anette
Abstract: Background: This secondary analysis of the Self‐Match Study explores whether personality traits affect the treatment outcome for alcohol use disorders (AUD). We designed the Self‐Match Study to investigate whether clients choosing between treatment options improves treatment outcomes. The primary outcome report revealed no difference in the outcome, whether treatment allocation was based on clinician matching or self‐matching. Because willingness to choose, choice of treatment method, and compliance with treatment may be related to personality, this exploratory sub‐study investigated the influence of personality traits on treatment outcome. Method: We enrolled 402 consecutive clients (female 46.7%, mean age 47.4) seeking treatment at the outpatient alcohol treatment center in Odense, Denmark. Clients were randomized to treatment by expert‐match or self‐matching. Data on alcohol consumption (Timeline Follow Back), personality traits (NEO‐FFI‐3), and retention in care were collected at baseline and 6‐month follow‐up. Outcomes were compliance, sensible drinking (alcohol intake below National Recommendations), and the number of heavy drinking days at follow‐up. Results: A high neuroticism score was negatively associated with treatment completion. Further, clients with a high score on neuroticism, openness, and extraversion, or a low score on conscientiousness were less likely to reduce their drinking to a sensible level at follow‐up. We also found that low scores on conscientiousness were associated with having more heavy drinking days at follow‐up. The personality traits neuroticism and openness were associated with treatment preferences. Conclusions: Personality traits influence 6 months drinking outcomes for people receiving AUD treatment. Abstract : Personality traits seem to not affect treatment completion. However, a high score on neuroticism, openness, extraversion, or a low score on conscientiousness influence the drinking pattern in different ways at 6‐month follow‐up. The personality traits neuroticism and openness were associated with preferences for specific treatment methods, but further research is needed on this matter. Tentative conclusions are that client‐centered treatment is preferable and shared decision‐making should be considered as part of the treatment regimen.